Tellurite Reduction by Escherichia Coli Ndh-Ii Dehydrogenase Results in Superoxide Production in Membranes of Toxicant-Exposed Cells - Vasquez-Guzman, C; Arenas-Salinas, F; Cornejo-Leiva, F; Díaz-Vásquez, W; Abarca-Lagunas, M (Kluwer Academic Publishers, 2014)
Tellurite, the most soluble tellurium oxyanion, is extremely harmful for most microorganisms. Part of this toxicity is due to the generation of reactive oxygen species that in turn cause oxidative stress. However, the way in which tellurite interferes with cellular processes is not well understood to date. Looking for new cellular tellurite targets, we decided to evaluate the functioning of the electron transport chain in tellurite-exposed cells. In this communication we show that the E. coli ndh gene, encoding NDH-II dehydrogenase, is significantly induced in toxicant-exposed cells and that the enzyme displays tellurite-reducing activity that results in increased superoxide levels in vitro. © 2014 Springer Science+Business Media.